Coding scheme for a power line communication channel: a comparative study / Jehana Ermy Jamaluddin and Ong Hang See - Jamaluddin, Jehana Ermy; Ong, Hang See (2006)
Designing a system that is able to withstand unpredictable events is truly a challenging task for data communication engineers. Power lines are potentially convenient and cheap for data transmission, nevertheless, their electrical signal transmission characteristics make it difficult to design even a simple modem. This paper presents the outcome of a study and analysis on various error correction codes to determine the most optimum and practical solution for power line medium. Standard channel model used for testing coding implementation and hardware design is yet to be established. Here, a model with local assumptions and settings is applied. The techniques currently applied are based on some assumptions and settings. The paper reports a compare and contrast of the gain, the bit error rate and the overall performance of the available techniques. Based on the outcome of this study, it is hoped that that more techniques can be discovered and, if not, hybrid techniques can be devised towards a better PLC realization.